Religion in Disputes
XX, 265 p.
Keywords: How are time-honored tenets of faith, different ritual sensibilities, and newly emerging eschatological imaginaries articulated with other normative registers and moral susceptibilities in disputes? This book examines such questions through cases in Europe, the United States, Israel, Africa, and South and Southeast Asia.